PERLINDUNGAN HUKUM TERHADAP DEBITUR WANPRESTASI YANG DIAKIBATKAN OLEH PANDEMI - Putu Pratama Wira Wira Adhyaksa; I Made Dedy Priyanto (Kertha Negara : Journal Ilmu Hukum, 2023)
The purpose of this study is to examine the problems that are happening in Indonesia, especially when the pandemi has hit like now. This study uses normative legal research methods with statutory and comparative approaches. The results of the study show that the government is taking a path to make new regulations as an effort to overcome the crisis that occurred in Indonesia, namely the issuance of OJK Regulation Number 11 /POJK.03/2020 concerning